PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN: PERSPEKTIF BALANCED SCORECARD - Geta Alviane; St. Vena Purnamasari (Universitas Katolik Soegijapranata Semarang, 2011)
This study examines the influence of Intellectual Capital (IC) on firm performance as measured by the perspective of Balanced Scorecard (BSC). BSC perspectives consists of 4: the cllstomer (measured by retention and clis/orner acquisition). internal business processes (measured by sales growth). learning and growth (measured by the prodllctivity of employees) and financial (measured by ROA and ROE). This stU(ZV took a sample of companies in Indonesia Slack Exchange in 2006-2009 as many as 45 companies The results showed Intellectual Capital (VAIC) does not affect compan performance in terms of customer perspective of BSC. Intellectual Capital (VAIC) did not affect company performance in terms of infernal business process perspective of BSC. Intellectual Capital (VAIC) did not afTect company performance in terms of learning and growth perspective of BSC. Intellectual Capital (VAIC) does not affect the performance of the company from the financial perspective of BSC. No significant effect of Intellectual Capital (VAIC) on perfonnance due to the human resources that are not capitalized into an asset but is charged.